Global Existence for Two Singular One-Dimensional Nonlinear Viscoelastic Equations with respect to Distributed Delay Term. (16th February 2021) - Choucha, Abdelbaki; Boulaaras, Salah Mahmoud; Ouchenane, Djamel; Allahem, Ali
Abstract : In this current work, we are interested in a system of two singular one-dimensional nonlinear equations with a viscoelastic, general source and distributed delay terms. The existence of a global solution is established by the theory of potential well, and by using the energy method with the function of Lyapunov, we prove the general decay result of our system.